Wilson disease: the diagnostic challenge and treatment outcomes in a series of 262 cases - Marta Mitiko Deguti; Fabiana Cordeiro Araujo; Débora Raquel Benedita Terrabuio; Thiago Ferreira Araujo; Egberto Reis Barbosa; Gilda Porta; Eduardo Luiz Rachid Cançado (Arquivos de Neuro-Psiquiatria)
Background Wilson disease (WD) is an autosomal recessive disorder that leads to organ toxicity due to copper overload. Early diagnosis is complicated by the rarity and diversity of manifestations.